2006
DOI: 10.1111/j.1751-0813.2006.tb13399.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleuropneumonia as a sequela of myelography and general anaesthesia in a Thoroughbred colt

Abstract: A 3-year-old Thoroughbred colt was presented to the University Veterinary Centre Camden for evaluation of ataxia. The horse was anaesthetised to facilitate cervical radiography and myelographic examination of the spinal cord. Recovery from anaesthesia was uneventful. Five days after general anaesthesia the horse re-presented with pleuropneumonia. It was euthanased 24 hours after presentation on humane grounds. Necropsy revealed severe tracheal erosion over the middle third of the ventral surface of the trachea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…These included 6 horses that were diagnosed with pneumonia. A case of pleuropneumonia occurred in a 3‐year‐old Thoroughbred 5 days after general anesthesia and cervical myelography . The colt was euthanized and a necropsy confirmed pleuropneumonia and identified severe erosions over the middle third of the trachea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These included 6 horses that were diagnosed with pneumonia. A case of pleuropneumonia occurred in a 3‐year‐old Thoroughbred 5 days after general anesthesia and cervical myelography . The colt was euthanized and a necropsy confirmed pleuropneumonia and identified severe erosions over the middle third of the trachea.…”
Section: Discussionmentioning
confidence: 99%
“…The colt was euthanized and a necropsy confirmed pleuropneumonia and identified severe erosions over the middle third of the trachea. Overinflation of the endotracheal tube cuff and manipulation of the neck are risk factors for damage to the tracheal mucosa and could have predisposed the colt to development of pleuropneumonia . Regardless of the mechanism of the development of pneumonia after cervical myelography, horses should be positioned carefully during the procedure to minimize injury and should be monitored closely postmyelography.…”
Section: Discussionmentioning
confidence: 99%
“…Rainger et al . () reported a case of tracheal erosion and subsequent pleuropneumonia following cervical myelography in a 3‐year‐old colt. It was concluded that flexion and extension of the neck during the procedure with an inflated cuffed ETT may have been a causative factor.…”
Section: Discussionmentioning
confidence: 99%
“…A case report [430] Post-anaesthetic myelomalacia (23) Postanesthetic poliomyelomalacia in a horse [431] (24) Hemorrhagic myelomalacia following general anesthesia in a horse [432] (25) Hematomyelia in a colt: A post anesthesia surgery complication [433] (26) Post-anaesthetic myelomalacia in a horse [434] Post-anaesthetic myelopathy (27) Post-anaesthetic myelopathy in a 3-year-old Friesian gelding [435] (28) Post anaesthetic myelopathy in the horse: A case report [436] Post-anaesthetic myopathy/neuropathy (22*) Postanesthetic equine myopathy suggestive of malignant hyperthermia. A case report [430] (20*) Hyperthermia and delayed-onset myopathy after recovery from anesthesia in a horse [428] (29) Suspicion of postanesthetic femoral paralysis of the non-dependent limb in a horse [437] Post-anaesthetic myositis (30) Tracheal reconstruction by resection and end-to-end anastomosis in the horse [438] Post-anaesthetic pleuropneumonia (31) Pleuropneumonia as a sequela of myelography and general anaesthesia in a Thoroughbred colt [439] Post-anaesthetic pulmonary haemorrhage (32) Fatal post-anaesthetic pulmonary haemorrhage in a horse suffering from chronic-active exercise-induced pulmonary haemorrhage [440] Prolonged recovery by HYPP (33) Postanesthetic recumbency associated with hyperkalemic periodic paralysis in a quarter horse [441] (19*) Hyperthermia during isoflurane anesthesia in a horse with suspected hyperkalemic periodic paralysis [427] Prolonged recovery by persistent hypoxaemia (34) Prolonged recovery from general anesthesia possibly related to persistent hypoxemia in a draft horse [442] Pulmonary oedema (35) Negative pressure pulmonary edema as a post-anesthetic complication associated with upper airway obstruction in a horse [443] (36) Pulmonary oedema associated with anaesthesia for colic surgery in a horse [444] (37) Suspected air embolism associated with post-anesthetic pulmonary edema and neurologic sequelae in a horse [445] (38) Pulmonary edema at recovery after colic operation with in-situ nasogastric tube in a horse [446] Tracheal rupture (39) Tracheal rupture following general anaesthesia in a horse [447] Total case reports = 39…”
Section: (12b) Case Reports Loe = 5 Referencesmentioning
confidence: 99%